1991
DOI: 10.1093/oxfordjournals.esr.a036576
|View full text |Cite
|
Sign up to set email alerts
|

Elite integration in stable democracies: a reconsideration*

Abstract: Efforts to reconeeptualize elite strueture and functioning in stable democracies, together with data from surveys of elite interaction networks in three demoeratie soeieties, suggest that the eonventional power elite, ruling class and pluralist perspeetives are only partly accurate and that fusing them in a more realistie model makes mueh sense. Using data from comparable surveys of national elites in the US, Australia and West Germany, we argue that the configurations of elite circles in these secieties revea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
0
8

Year Published

1998
1998
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(42 citation statements)
references
References 28 publications
0
34
0
8
Order By: Relevance
“…Higley and Burton (2006) (Higley et al, 1991). New elitists propose a typology of elite configuration: elites could be (a) disunited, (b) consensually united or (c) ideologically united.…”
Section: The New Elite Paradigmmentioning
confidence: 99%
“…Higley and Burton (2006) (Higley et al, 1991). New elitists propose a typology of elite configuration: elites could be (a) disunited, (b) consensually united or (c) ideologically united.…”
Section: The New Elite Paradigmmentioning
confidence: 99%
“…The densely connected core of directors was therefore identified as the inner circle of a national elite that integrates across regional and other societal divides (Useem, 1984). The very limited number of comparative investigations suggests that Germany also has a highly integrated and cohesive elite that interconnects across all societal spheres (Higley, Hoffmann-Lange, Kadushin, & Moore, 1991). Yet, empirical research has long ignored the broader links of the corporate elite.…”
Section: Elite Network and The Interlocking Of Organizational Boardsmentioning
confidence: 99%
“…Through membership network analysis, Domhoff (1998) discovered that individuals serving as directors on the same corporate boards formed interpersonal networks. In a comparative study of Australia, the United States (US), and Governance networks 4 Western Germany, Higley et al (1991) found the existence of densely connected circles of several hundred top leaders in each nation. Additionally, Unseem (1984), in a study of corporate directors in the US and UK, demonstrated the key role held by an inner circle of directors with interlocking directorships in leading corporations and nonprofit boards.…”
Section: Background: Network and Governance Of Corporations And Nonpmentioning
confidence: 99%